PENGARUH PEMBERIAN FUNGISIDA BENOMIL DENGAN DOSIS YANG BERBEDA DAN LAMA PENYIMPANAN TERHADAP KUALITAS BENIH Indigofera sp. - Rangga Bima Zunata; Muhtarudin Muhtarudin; Liman Liman; Erwanto Erwanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the effect of benomyl fungicide with different doses and storage time on the quality of Indigofera sp. This research was conducted in April – July 2021 at the Nutrition and Animal Feed Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a completely randomized design (CRD) with a factorial pattern (4 x 3) with the first treatment being the dose of the fungicide benomyl P0, P1, P2, and P3 (0%, 2%, 4%, and 6%) and the second treatment was duration storage T1, T2, and T3 (1, 2, and 3 months). Parameters observed were germination, normal germination, abnormal germination, hard seeds, dead seeds, and seeds attacked by pests. The data obtained were analyzed using analysis of variance (ANOVA) with a level of 5% and the least significant difference further test (LSD) was performed on the data which showed significantly different results. The results showed that there was no interaction between the dose of benomyl fungicide and the storage time on the quality of Indigofera sp. The best dose of benomyl fungicide for seed storage of Indigofera sp. was treatment P1 (2 mg/gr), because treatment P1 resulted in the highest percentage of gemination potency and normal germination and resulted in a low percentage of seeds attacked by pests. The best storage time for storing Indigofera sp seeds was treatment T1 (storage time of 1 month) because treatment T1 produced the highest percentage of germination and normal germination, which was 9.77% and 4.39%, respectively. Keywords: Benomyl fungicide, germination, Indigofera sp.